A Zinc–Cerium Cell for Energy Storage Using a Sodium‐Ion Exchange Membrane. (26th July 2017) - Yu, Xingwen; Manthiram, Arumugam
Abstract : The redox flow battery with a zinc–cerium (Zn–Ce) chemistry has been developed for about 10 years. Under the traditional battery development principle, a Zn–Ce cell has to be operated with an acidic electrolyte to sustain the redox reactions of Ce compounds (Ce(IV) ↔ Ce(III)) at the positive electrode. However, the use of an acidic electrolyte poses a serious corrosion issue on Zn and limits the electrochemical potential of the Zn electrode. Here, a novel Zn–Ce battery is presented with an alkaline electrolyte at the negative electrode side (anolyte) and an acidic electrolyte at the positive electrode side (catholyte). The two different‐pH liquid electrolytes are separated by a sodium‐ion (Na + ‐ion) solid‐electrolyte separator. The Na + ‐ion, shuttling through the solid electrolyte, is not involved in the redox reactions but rather acts as an ionic mediator to sustain the redox reactions at the negative and positive electrodes. Use of an alkaline anolyte not only eliminates the Zn corrosion problem but also enhances the cell voltage of the Zn–Ce system. In addition, the use of a solid electrolyte prevents the crossover of the liquid electrode materials (Ce(IV) or Ce(III)) and circumvents the concerns of Zn dendrite penetration. Abstract : A "mediator‐ion" solid electrolyte enables the operation of zinc–cerium batteries with an alkaline anolyte and an acidic catholyte. The battery development strategy overcomes the Zn corrosion problem, enhances the cell voltage, prevents the crossover of liquid electrode, and circumvents the zinc dendrite issue.